Kolaborasi Pendidikan Islam dan Teknologi dalam Manajemen Pendidikan Modern - Fatmaya Anisa Rahmania; Alya Mahirotun Numa (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The collaboration between Islamic education and technology has brought significant transformations in modern educational management. This study aims to analyze the integration of technology in Islamic education to enhance learning effectiveness, accessibility, and the relevance of the education system in the digital era. The research employs a qualitative literature review method by analyzing publications from 2020 to 2025. The findings indicate that technology, such as e-learning platforms and interactive applications, can enhance student engagement, expand geographical reach, and support the development of adaptive curricula based on Islamic values. However, major challenges include technological infrastructure gaps in remote areas, cultural resistance to change, and educators' limited digital competencies. This study highlights the importance of multidisciplinary collaboration among the government, educational institutions, and the technology industry to optimize the benefits of integration while preserving spiritual and moral values. Strategic recommendations include investment in digital infrastructure, practice-based teacher training, and the development of policies that integrate technological innovation with Islamic principles. The significance of this research lies in its contribution to mapping the opportunities and challenges of Islamic education transformation while providing a strategic framework for stakeholders to establish an adaptive and character-driven education system.